Giant Leiomyoma of the Retzius Space: A Case Report - Franco Pepe; Pietro Pepe; Filippo Rapisarda; Marta Fauzia; Maria Giunta (Case Reports in Obstetrics and Gynecology)
Extrauterine leiomyoma is a very rare clinical condition; we report a case of leiomyoma of the Retzius space in a 49-year-old women who suffered for two years from bladder voiding symptoms characterized by dysuria, feeling of incomplete emptying, and pelvic pain. Clinical evaluation and abdominal and transvaginal ultrasound suggested the presence of a voluminous (about 10 cm in diameter) fibromyoma of the anterior uterus surface. The urodynamic evaluation demonstrated the presence of bladder outlet obstruction (voiding pressure greater than 20 cm H2O and maximum flow rate less than 12 mL/s) with a postvoiding urine residual equal to 80 mL; moreover, the presence of cystocele and urethral stricture was ruled out performing clinical evaluation, cystography, and cystourethroscopy. The patient underwent laparotomy to remove the uterine fibromyoma. Intraoperatively, a voluminous soft mass arising from the Retzius space was found; it was firmly adhered to the uterus with obliteration of vesicouterine pouch owing to severe adhesion to the anterior surface of uterus. The tumour was isolated, enucleated from the prevesical space, and removed; moreover, the patient became asymptomatic after surgery. In conclusion, leiomyoma of the Retzius space is a very rare benign tumour that should be considered in the presence of severe bladder voiding symptoms.